2010
DOI: 10.1097/mph.0b013e3181c80bf3
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-associated Intracranial Leiomyosarcoma in an HIV-positive Adolescent

Abstract: A 17-year-old African American female with human immunodeficiency virus infection presented with an unresectable intracranial neoplasm with mass effect upon the brainstem. Stereotactic biopsy revealed an Epstein-Barr virus (EBV)-associated leiomyosarcoma. Radiation therapy and gemcitabine were used to shrink the mass with the aim to make it surgically resectable. Prolonged neutropenia and recurrent skin infections led to the discontinuation of gemcitabine. The mass stabilized after radiation therapy and has de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…It may be that LMP expression is below that detected by immunohistochemistry in these tumors. Although there were some inconsistent results in cases tested for EBNA-2 and LMP-1 [7, 19, 20, 22, 27, 30, 45], it would appear that overall EBV-SMT demonstrate Type III latency. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that LMP expression is below that detected by immunohistochemistry in these tumors. Although there were some inconsistent results in cases tested for EBNA-2 and LMP-1 [7, 19, 20, 22, 27, 30, 45], it would appear that overall EBV-SMT demonstrate Type III latency. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, each lesion is likely a separate infection event. Studies looking at EBV copy numbers in EBV-SMT have found variable results and it has been suggested that this variation is the result of EBV being present in the lytic or latent phase [2, 7, 8]. One could expect that patients with active replicating EBV will have EBV detectable in their serum [18, 22, 25, 32, 33].…”
Section: Resultsmentioning
confidence: 99%
“…3,8,10 The role of immunosuppression in the pathogenesis of EBV-SMT in patients infected with HIV/AIDS has been documented. 1,6,11 Long-standing low CD4 count and a high viral load may encourage tumor growth and enhance the possibility of tumor recurrence. 1 These tumours are commonly multifocal 3,8,10 and vary in description from ''leiomyoma'' to ''smooth muscle tumor of uncertain malignant potential'' to ''leiomyosarcoma'' reflecting the different criteria of malignancy utilized by various authors to histologically classify these tumours.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,11 Long-standing low CD4 count and a high viral load may encourage tumor growth and enhance the possibility of tumor recurrence. 1 These tumours are commonly multifocal 3,8,10 and vary in description from ''leiomyoma'' to ''smooth muscle tumor of uncertain malignant potential'' to ''leiomyosarcoma'' reflecting the different criteria of malignancy utilized by various authors to histologically classify these tumours. 8,11 The presence of only moderate cytologic atypia and an average mitotic count of 0/10 HPF may categorise the tumour in our patient as a benign leiomyoma.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 20/37 (54.1%) patients who received postoperative radiotherapy, the dosage, fractionation, administration methods, and tumor responses achieved were not well documented. For7/37(18.9%)patientswhoreceived chemotherapy, the chemotherapy regimens included the administration of vincristineandprocarbazine [13],doxorubicinalone [17,23],acombinationof ifosfamide, carboplatin, and etoposide [26], a combination of vincristine, ifosfamide,doxorubicin,andetoposide [27], orgemcitabinealone [28].…”
Section: Histopathologymentioning
confidence: 99%